2016
DOI: 10.1007/s12035-016-9928-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of the Long Noncoding RNA NEAT1 in Huntington’s Disease

Abstract: Huntington's disease (HD) is a devastating neurodegenerative disease caused by cytosine-adenine-guanine trinucleotide repeat expansion in the huntingtin gene. Growing evidence supports the regulatory functions of long noncoding RNAs (lncRNAs) in the disease process, but little is known about the association between lncRNAs and neuronal death in HD. Here, we evaluated the altered expression profiles of lncRNA in HD by using microarrays. Among dysregulated lncRNAs, we focused on the upregulation of nuclear paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 49 publications
5
123
0
Order By: Relevance
“…One such example is NEAT1, which is critical for synapse formation in the brain (Sunwooet al, 2017), whereas, in adipose tissue, NEAT1 is necessary for the differentiation of white adipocytes (Cooper et al, 2014). lincRNA-Cox2 KO and mutant mice were used to globally study the cis and trans role of lincRNA-Cox2 in vivo by performing RNA-seq on lungs and spleens from LPS-challenged WT, KO, and mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…One such example is NEAT1, which is critical for synapse formation in the brain (Sunwooet al, 2017), whereas, in adipose tissue, NEAT1 is necessary for the differentiation of white adipocytes (Cooper et al, 2014). lincRNA-Cox2 KO and mutant mice were used to globally study the cis and trans role of lincRNA-Cox2 in vivo by performing RNA-seq on lungs and spleens from LPS-challenged WT, KO, and mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, there is also a strong link between high NEAT1 expression and more aggressive forms of cancer (Chakravarty et al 2014;Chai et al 2016;Chen et al 2016;Fu et al 2016;Ma et al 2016;Sun et al 2016;Wang et al 2016). In neurological systems, up-regulated expression of NEAT1 has also been observed in the early phase of amyotrophic lateral sclerosis and Huntington's disease, and more interestingly, its expression could also be acutely down-regulated in response to neuronal activity (Nishimoto et al 2013;Sunwoo et al 2016;Barry et al 2017). At the molecular level, NEAT1 is important for the formation of paraspeckles, a type of mammalian nuclear RNA-protein body found in close proximity to nuclear speckles (Fox et al 2002;Hutchinson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, NEAT1 also affects mitochondrial abundance and function (23). Nuclear paraspeckles have been identified as causally involved in immune responses (24) and cancer (25), and recent research on NEAT1 functions in the context of the CNS has revealed its involvement in Huntington’s disease (26) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)–induced neurotoxicity (27, 28). However, although the involvement of NEAT1 in PD has been suggested in animal models of neurodegeneration, they have not yet been thoroughly examined in human disease.…”
mentioning
confidence: 99%